STUDI KUALITAS AIR BERDASARKAN PARAMETER FISIKA DAN KIMIA PADA AIR GUA DESA LABURUNCI KABUPATEN BUTON - Ni'ma Meilani; Sadam Sudin Sahi (Jurnal Kesehatan Manarang, 2017)
Water is a basic requirement for human life. Clean water sources used by village communities apart Laburunci comes from taps Kabupaten Buton also sourced from springs Caves Village Laburunci. Recorded in March 2015 as many as 235 households use water cave, but until now there has been no student or institutions that conduct scientific research to determine the water quality of the cave. This study aims to determine the water quality of Cave Village Laburunci Buton based on physical and chemical parameters. This type of research is observational dekskriptif, a total sample of 149 with a simple random sampling technique. The research instruments were questionnaires, observation sheets, and laboratory instruments. Research results from the analysis based on the Minister of Health No. 416/Men.Kes/Per/IX/1990 concerning requirements and Water Quality Monitoring. The results showed that for the physical parameters, the artist smell is known of the 149 respondents stating no smell. This is in contrast to the parameters of taste and color where there are two respondents stated that taste and a third of respondents stated that colorless. For chemical parameters such as pH and DO is known that the pH value of the water cave at 7.87 while DO is at 7.3 mg/l. Thus we can conclude that both physical parameters and chemical parameters, based Permenkes No. 416/Men.Kes/Per/IX/1990 concerning requirements and Monitoring Water Quality, Air Caves Village Laburunci eligible for use in meeting the needs of the household. Laburunci need for villagers, village government and related agencies to work together to protect water quality Laburunci Gua village located in the village of Laburunci Buton.